The minimum dietary diversity for women indicator can be extended to children and adolescents aged 4-15 years as a proxy population indicator for good micronutrient adequacy of diets in low- and middle-income countries - Diop, Loty; Gelli, Aulo; Huybregts, Lieven; Arsenault, Joanne E.; Bliznashka, Lilia; Boy, Erick; Deitchler, Megan; Lachat, Carl; Moursi, Mourad; Ochoa-Avilés, Angelica M.; Olney, Deanna K.; Becquey, Elodie (Elsevier, 2025)
Background The response to the global call for more data on children’s and adolescents’ diets and nutrition is limited by the lack of straightforward practical indicators to track their diet quality. On the basis of a food group score compiled from 10 food groups (FGS-10), the minimum dietary diversity for women, calculated as FGS-10 ≥ 5, is a validated proxy population indicator for better micronutrient intake adequacy for adult women in low- and middle-income countries (LMICs). Objectives This study aims to validate FGS-10 and its related cutoffs against micronutrient intake adequacy in 4–15-y-old children/adolescents in LMICs. Methods We conducted a secondary data analysis of 9 datasets of repeated 24-h recalls or weighed records including 11,524 children/adolescents aged 4–15 y, collected in 7 countries (Burkina Faso, Ghana, Ecuador, India, Malawi, Uganda, and Zambia) between 2007 and 2022. For each dataset and the pooled sample (meta-analysis), we assessed the association between FGS-10 and the mean probability of adequacy (MPA) of intake over 8 micronutrients (MPA-8), and the performance of several FGS-10 cutoffs in predicting acceptable (≥0.60) and good (≥0.80) levels of MPA-8. Robustness analyses used the 7 datasets with data on 11 micronutrients (MPA-11). Results FGS-10 ranged from 3.0 to 4.8 across datasets, and the proportion of children/adolescents with acceptable MPA-8 ranged from 8.4% to 74%. Positive and significant associations between FGS-10 and MPA-8 were found in all datasets and the pooled sample. The optimal cutoff varied across datasets from FGS-10 ≥ 4 to FGS-10 ≥ 6. In the pooled sample, FGS-10 ≥ 5 had the highest performances in predicting acceptable and good levels of MPA-8. FGS-10 ≥ 5 was also the best proxy indicator for MPA-11 ≥ 0.80. Conclusions The continuous FGS-10 and dichotomous FGS-10 ≥ 5 may be extended to 4–15-y-old children/adolescents in LMICs. In this population, FGS-10 ≥ 5 can be used as a proxy population indicator for good micronutrient adequacy of diets.